Preliminery Research Phase Analysis as a Basis for Developing a Plant Morphology Practical Guidebook Based on a Scientific Approach - Fauziah, Nurul; Ferazona, Sepita; Sulistiawati, Dea (Edunesia : Jurnal Ilmiah Pendidikan, 2024)
This research was motivated by problems in practicum activities that the researcher found as a lecturer teaching plant morphology courses, one of which was that the plant morphology practicum did not have a practicum manual that was able to hone students' science process skills. The aim of this research is to describe preliminery research phase data obtained as a basis for developing a plant morphology practicum guidebook based on a scientific approach. This type of research is development research using the Plomp development model, the research only reached the first stage, namely the preliminery research phase. The number of sampels in this study was 96 biology education students at FKIP UIR. The research instruments are RPS analysis sheets, interview sheets, observation sheets, problem and needs questionnaires. The results of the research revealed that from the RPS analysis there were 6 topics that would be put into practice, 10.83% state the practical guidebook was not based on a scientific approach, and based on the needs questionnaire, 100% of students agreed that it was necessary to develop a plant morphology practical guidebook based on a scientific approach. It can be concluded that based on preliminery research phase data, it is necessary to develop a practical guidebook for plant morphology based on a scientific approach. The expected implication of this research is that after the plant morphology practicum manual based on a scientific approach passes tests of validity, practicality and effectiveness, that can improve practicum learning outcomes and hone students' science process skills.